1994
DOI: 10.1210/jcem.78.2.7906279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a new oral somatostatin analog (SDZ CO 611) on gastric emptying, mouth to cecum transit time, and pancreatic and gut hormone release in normal male subjects.

Abstract: Sixteen healthy male volunteers participated in a randomized, double blind, parallel groups study. Subjects received either 1 or 5 mg SDZ CO 611 (a new, orally active somatostatin analog) twice daily over a 14-day period and acted as their own controls. Gastric emptying of 99mTc and mouth to cecum transit time, as measured by the breath hydrogen technique, after a mixed meal containing lactulose and 99mTc-diethylenetriaminepentaacetate, were assessed once before, twice during, and once after the period of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Somatostatin analogues are an effective treatment option for patients with well‐established dumping syndrome who fail to respond to and/or do not tolerate initial dietary modification and acarbose treatment. Somatostatin analogues target various steps in the pathophysiology of dumping syndrome, including delaying gastric emptying, delaying transit through the small intestine, inhibiting the release of GI hormones, inhibiting insulin secretion and inhibiting postprandial vasodilation . Somatostatin inhibition of GLP‐1 secretion is mediated via activation of the somatostatin receptor subtype (sst) 5, with a lesser effect through sst2 .…”
Section: Treatmentmentioning
confidence: 99%
“…Somatostatin analogues are an effective treatment option for patients with well‐established dumping syndrome who fail to respond to and/or do not tolerate initial dietary modification and acarbose treatment. Somatostatin analogues target various steps in the pathophysiology of dumping syndrome, including delaying gastric emptying, delaying transit through the small intestine, inhibiting the release of GI hormones, inhibiting insulin secretion and inhibiting postprandial vasodilation . Somatostatin inhibition of GLP‐1 secretion is mediated via activation of the somatostatin receptor subtype (sst) 5, with a lesser effect through sst2 .…”
Section: Treatmentmentioning
confidence: 99%
“…A series of studies employing Northern blot, RT-PCR and in situ hybridization analysis has revealed complex gene typespecific expression patterns in many regions of the central nervous system (CNS) and peripheral tissues. The areas of intensive somatostatin receptor expression include the hypothalamic-hypophyseal system, which regulates the adenohypophyseal release of GH, TSH and prolactin (Brazeau et al, 1972), the widespread somatostatinergic system in the CNS modulating many cognitive and vegetative functions and references therein) and the gastroenteropancreatic system of neuroendocrine cells that regulates gastric acid and gastroenteropancreatic hormone release (Nelson-Piercy et al, 1994). Furthermore, a recent study revealed temporally and spatially regulated expression patterns of SSTR2 and SSTR4 during embryonic development of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Other actions on gastrointestinal motility are the inhibition of antral motility, the induction of phase III like activity of the migrating motor complexes in the interdigestive state, and prolongation of the mouth to caecum transit time (MCTT) 2223 25 26 These studies, which addressed the effect of octreotide on gastric emptying, tested the effect of a single low dose (50 μg) subcutaneously, or oral doses of octreotide 2223 In an experimental study of the effect of octreotide on postoperative ileus in dogs, Cullen et al found a delay in gastric emptying for a dosage scheme of 0.83 μg/kg/h in continuous subcutaneous infusion 27.…”
mentioning
confidence: 99%